Antibacterial Activity of Bioactive Compounds of Green Coffee Beans on Periodontogenic and Nosocomial Bacteria - Tripathi, Shraddha; Mishra, Neha; Mishra, Neetu (Journal of Pharmacy and Nutrition Sciences, 2022)
The emergence of antimicrobial resistance and the side effects of synthetic drugs have raised an interest in searching for new antimicrobial compounds. The present study aims to evaluate in vitro antibacterial activity of green coffee and its active compounds (chlorogenic acid extract and caffeine extract) against some periodontogenic and nosocomial bacteria. The bioactive compounds, viz. chlorogenic acid and caffeine, were extracted through soxhlet extraction using methanol and water, respectively, and HPLC UV quantified these compounds. The study reported 3 CQA, 4 CQA, and 5 CQA as the significant chlorogenic acids in green coffee beans. Aqueous extract of green coffee beans (AGCB), which is dominant in caffeine, has been found to be the least effective against both periodontal and nosocomial bacteria. The result of our study revealed that the methanol extract of green coffee bean (MGCB), rich in chlorogenic acid, exhibits the highest inhibitory activity against periodontogenic bacteria, followed by the ethanol extract of green coffee bean (EGCB) and AGCB extract. EGCB extract was significantly effective against Staphylococcus epidermidis among selected nosocomial pathogens. AGCB extract was least effective against all bacteria. The results highlight that green coffee polyphenols, especially chlorogenic acid, could be used as antimicrobial agents in different biotechnological applications. The antibacterial property of green coffee highlights its potential as a naturally active antibacterial compound.